Richardson Extrapolation : Practical Aspects and Applications. - Zlatev, Zahari (De Gruyter series in applied and numerical mathematics., 2017)
Scientists and engineers are mainly using Richardson extrapolation as a computational tool for increasing the accuracy of various numerical algorithms for the treatment of systems of ordinary and partial differential equations and for improving the computational efficiency of the solution process by the automatic variation of the time-stepsizes. A third issue, the stability of the computations, is very often the most important one and, therefore, it is the major topic studied in all chapters of this book. Clear explanations and many examples make this text an easy-to-follow handbook for applied mathematicians, physicists and engineers working with scientific models based on differential equations. ContentsThe basic properties of Richardson extrapolationRichardson extrapolation for explicit Runge-Kutta methodsLinear multistep and predictor-corrector methodsRichardson extrapolation for some implicit methodsRichardson extrapolation for splitting techniquesRichardson extrapolation for advection problemsRichardson extrapolation for some other problemsGeneral conclusions